Future Climate Change Shifts the Ranges of Major Encroaching Woody Plant Species in the Southern Great Plains, USA - Jia Yang; Rodney Will; Lu Zhai; Chris Zou (Earth's Future)
Abstract Woody Plant Encroachment (WPE) is a key driver of grassland collapse in the Southern Great Plain (SGP), resulting in a series of adverse ecological and socioeconomic consequences. Climate change will interact with ongoing WPE as it will likely shift the potential ranges of WPE species. In this study, we employed an ensemble approach integrating results from multiple Species Distribution Models to project future distribution ranges of four major WPE species (Ashe juniper, honey mesquite, post oak, and eastern redcedar) in the SGP across the 21st century. The findings highlighted a noteworthy trend: under future climate conditions, the distribution ranges for these WPE species were projected to shift northward and eastward. Of particular concern is honey mesquite with significant expansion in distribution range, potentially covering up to two‐thirds of the SGP's non‐agricultural area by the end of the 21st century. Conversely, the other three WPE species were expected to experience a contraction in their distribution ranges. Ashe juniper may experience a decline in its current habitats in central Texas but gain new habitats in northern Texas, Oklahoma, and Kansas. The suitable ranges of post oak and eastern redcedar were projected to shrink eastward, primarily being restricted to eastern portions of Oklahoma and Texas under the RCP4.5 and a smaller area in eastern Oklahoma under the RCP8.5. The projected shift in WPE ranges provides a scientific basis for governments to optimize the allocation of management resources and implement timely practices to control the spread of woody plants during the early encroachment stage. Our study methodology is applicable to other regions and continents with WPE issues, including Africa, South America, and Australia.